Dynamic and Stable Core Microbiota Assist Plants in Enriching Selenium and Reducing Cadmium Absorption - Zheng Lei; Hua Zhang; Wenju Liu; Jiandong Sheng; Huan Zhang; Yin Wang; Yanni Tang; Huaxing Wang; Cuicui Ding; Wanqi Qiao; Yonghui Zhu; Guoyin Yang; et al. (Advanced Science)
Abstract Rhizosphere microbiome is crucial for regulating rhizosphere complex nutrient dynamics. However, mechanisms by which plants regulate rhizosphere microbes to manage nutrient availability under coexisting beneficial and harmful elements remain unclear. This study focuses on the rhizosphere microbiome of Brassica napus in different naturally selenium (Se)–cadmium (Cd)‐rich soils, the functionality of this rhizosphere, and the changes in the availability of rhizosphere nutrients. Microbiome analysis, metagenomics, genomic analysis, strain isolation, and functional validation are performed to investigate these relationships. Results show that a significant negative correlation is observed between the rhizosphere available Se and Cd content across the plant whole growth cycle and identified a group of core microbiota that are highly positively correlated with available Se and negatively correlated with available Cd. Genomics and metagenomics analyses reveal that the core microbiota has a higher substrate preference for amino acids related to the glutathione metabolic pathway. Key glutathione‐related‐amino acids and synthetic microbial community significantly improve the expression of glutathione anabolism and related amino acid transport genes and enhance Se uptake and reduce Cd absorption in plants grown in various Se‐Cd‐rich soils. This study provides insights into the mechanisms of root‐associated microbes responding to complex soil nutrients during plant growth.